(untitled) (International Journal of Food and Nutritional Sciences, 2022)
We reside in a rapidly expanding globe, and with it, the availability of transport options. Travel agencies compete with one another in every region of the world to offer their clients the best amenities. One of the largest networks in the hamlet is centred around the minibus service. Under one administration, it is Tamilnadu’s main transport system. For millions of residents in the community, it is the most practical and affordable form of transportation. The mini bus’s most lucrative market is its passenger support section. Both the passengers and the revenue are directly impacted by the minibus operations. The passenger-oriented sector and passenger traffic in the Tenkasi district segment produce substantial revenue. Understanding the expectations and opinions of passengers regarding the calibre of services offered by the mini bus is crucial in order to give individualised services. The survey considers commuters’ satisfaction with the various services provided by the micro bus service. The main source is information gathered from 100 passengers at Tenkasi, Pavoorchathiram, Alangulam, Surandai, and Kadaiyam using a structured questionnaire.